1990
DOI: 10.1073/pnas.87.13.5129
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of protein-DNA interactions in the proximal promoter of a cell-growth-regulated histone gene during onset and progression of osteoblast differentiation.

Abstract: A temporal sequence of interrelated cellular, biochemical, and molecular events which occurs during the progressive expression of the differentiated osteoblast phenotype in primary cultures of fetal rat calvarial cells results in the development of a bone-tissue-like organization. This ordered developmental sequence encompasses three periods: proliferation, matrix maturation, and mineralization. Initially, the cells actively proliferate and synthesize type I collagen. This is followed by a period of matrix org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…The correlation between cessation of cell proliferative activity, transcriptional downregulation of histone gene expression, and loss of HiNF-D binding activity is also evident in other cell culture systems, including during differentiation of primary rat calvarial osteoblasts (40) (28). Similarly, nuclear factor HiNF-A, which recognizes AST-rich DNA sequences in histone H4, H3, and Hi promoters, is a cell cycle-independent DNA-binding protein irrespective of cell type (61 (26,44) and genomic protection assays (42,51).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The correlation between cessation of cell proliferative activity, transcriptional downregulation of histone gene expression, and loss of HiNF-D binding activity is also evident in other cell culture systems, including during differentiation of primary rat calvarial osteoblasts (40) (28). Similarly, nuclear factor HiNF-A, which recognizes AST-rich DNA sequences in histone H4, H3, and Hi promoters, is a cell cycle-independent DNA-binding protein irrespective of cell type (61 (26,44) and genomic protection assays (42,51).…”
Section: Discussionmentioning
confidence: 91%
“…2B) Table 1 for references containing experimental details and supporting data). Factor HiNF-D has been isolated from a broad spectrum of proliferating cell types in our laboratory (3,23,40,57,58,64,71), as well as other laboratories (23,58,71) (27,29,38,44 (7) genes, although expression of a variant poly(A)+ H2B gene is increased (6). Therefore, these results for H4 site II in vivo and HiNF-D in vitro demonstrate that selective modifications occur in protein-DNA interactions when histone gene transcription is modulated.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation by protein kinase C and casein kinase II or PCAF-mediated acetylation of the CDP/Cux homeodomain inhibits DNA binding activity (6,8,21). Stable CDP/Cux-DNA complexes are detected in proliferating cells but disappear upon cellular differentiation of HL60 promyelocytic leukemia cells and fetal rat calvarial cells (22,27,28). CDP/Cut has been shown to bind to a variety of promoters or enhancer sequences of genes involved in differentiation, including myeloid cytochrome gp91-phox (28), dog heart myosin heavy chain (1), rat tyrosine hydroxylase (50), human ␥-globin (33), Xenopus ␤-globin, and mouse N-CAM (36).…”
mentioning
confidence: 99%
“…ALP, a precocious marker of osteogenetic differentiation, is found in high quantities in the cells in the phase ofmineralization ofthe matrix, as are the osteoblasts (24). Recent studies have demonstrated that the physical and chemical characteristics of the implant surface influence the adhesion, proliferation, differentiation and maturation of bone celt's (25)(26).…”
Section: Resultsmentioning
confidence: 99%